The Political Economy of the Most Radical Reform of the Common Agricultural Policy - Jo Swinnen (German Journal of Agricultural Economics (GJAE), 2010)
The 2003 reform of the European Union's Common Agricultural Policy (CAP) under Commissioner Fischler was the most radical in the history of the CAP. This paper analyzes the causes and constraints of the 2003 reform. The paper argues that an unusual combination of pro-reform factors such as institutional reforms, changes in the number and quality of the political actors involved in the reform process, and strong calls to reform from external factors came together in the first few years of the 21st century, allowing this reform to be possible.
Keywords: 330